Effect of Energy Management of a Grid Connected Photovoltaic/Battery/Load System on the Optimal Photovoltaic Placement on a National Scale: The Case of Turkey - Akdemir, Huseyin; Durusu, Ali; Erduman, Ali; Nakir, Ismail (ASME, 2018)
Photovoltaic (PV) hybrid systems and their optimal energy management are still being actively studied. PV systems must be positioned at optimal tilt and azimuth angles to obtain maximum system performance. This paper presents the effect of energy management of a grid-connected PV-battery-load system on optimal PV placement using a linear programing (LP) method. The optimal placement of PV arrays aims to minimize the electricity cost of a fixed PV system for investors by considering monthly average daily global radiation, ambient temperature, wind speed, demand management constraints, and electricity tariffs in Turkey. The analysis is extended to consider 68 locations across Turkey. The analysis reveals that the optimal placement (optimal tilt and azimuth angle) can be different from that of previous studies because of multiple objective considerations. The optimal tilt angle results are lower than the local latitude in the range of 0 deg-8 deg in all regions. Furthermore, the optimal azimuth angle results are in the range of 6 deg-24 deg westbound throughout Turkey. These results can play a significant role for investments in the design of grid-connected PV-battery-load systems.
Keywords: TILT ANGLE; SOLAR-RADIATION; ORIENTATION; STORAGE; MODEL; Energy & Fuels; Engineering